Mediatisasi Politik dan Personal Branding Agus Harimurti Yudhoyono Melalui Media Sosial Instagram - Patria, Laskarko (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Agus Harimurti Yudhoyono (AHY) is the youngest candidate for president or vice president, it is necessary to maximize communication strategies through Instagram in gaining support from young voters. This study uses the Post-Positive Paradigm, with the basis of Agenda Setting theory, Personal Branding theory, Mediatization theory, as well as with a Qualitative-Descriptive research approach. Data Analysis Techniques using Framing Analysis (Zongdang Pan & Gerald M. Kosicki) and qualitative data analysis techniques developed by Miles & Huberman. Methods of data collection using observation, and documentation. Data obtained directly from AHY's Instagram accounts, and observations. AHY reported on his activities, social action activities, family, and political activities, in the form of photos and videos through Instagram @agusyudhoyono social media. In the framing of this research, Agus Harimurti Yudhoyono is a political figure who has national values, is firm, a fairly good young politician, a young leader who is admired by young people, has a nationalist spirit, and is a humanist figure. In Personal Branding, Agus Yudhoyono is known and admired by the younger generation as a young political figure, well-groomed, charismatic, handsome, and authoritative.